Efforts To Improve Students Ability Answering Fill In Fairy Tale With Good Through Exercise In Class Iii Sd Negeri 33 Desert Long District Of Koto Xi Tarusan Academic Year 2016/2017 - Ernawati Ernawati (Jurnal Ilmiah Pendidikan Scholastic, 2017)
This study was designed through Action Research (PTK). The purpose of research this is for knowing enhancement Results ability to answer contents of a fairy tale. Classification of Indonesian learning through the application of learning models of storytelling to enhance the ability of story telling in the class III SD Negeri 33 Desert Long District of Koto XI Tarusan in the academic year 2016/2017 . The subjects were class III Elementary School 33 Long Desert District of Koto XI Tarusan in the academic year 2016/2017 the number of students 21 people. This study was conducted in three cycles. Each cycle consists of four phases: planning ( planning ), implementation ( acting ), observation ( observing ) and reflection ( reflecting ). Learning Indonesian is part of the reading well which emphasizes providing direct experience. During this time students' difficulties increase ability to answer contents fairytale because many got good at story telling students not to use Indonesian Better. To help his students raise the n ability to answer contents of a fairy tale, then applied learning storytelling learning model that varied with LKS. Indicator success research this are: 1) Increased percentage Students that Earn value ≥65 or the number of students that b elajar due to increase to 85%. 2) The completeness liveliness classical ≥75%. Based on Results research The obtained data increase the percentage of achievement of classical learning completeness in the first cycle 77, 5% and the second cycle of 87.5%, while the activity of classical pad a cycle I Cycle II 61.25% and 76.25%. The conclusion from this study that through the application of learning models of story telling with improving literacy in Indonesian Classification material can improve results Storytelling ability of students in class III. While this study is the suggestion should Storytelling learning model to enhance the ability Storytelling be applied to materials that Indonesian another as a model of learning by improving the ability Storytelling Make it easy Students in understanding the material being studied.